Change in Hydrogen-Storage Performance of Transition Metals and NaAlH4-Added MgH2 with Thermal and Hydriding-Dehydriding Cycling - Seong Ho Lee; Hye Ryoung Park; Myoung Youp Song (대한금속재료학회지, 2015)
A sample with a composition of 86 wt% MgH2-10 wt% Ni-2 wt% NaAlH4-2 wt% Ti (designated MgH2-10Ni-2NaAlH4-2Ti) was prepared by reactive mechanical grinding. The sample was subjected to thermal cycling (between room temperature and 623 K) as well as cycling between hydriding (at 593 K under 12 bar H2) and dehydriding (at 623 K in vacuum). At n=1, MgH2-10Ni-2NaAlH4-2Ti absorbed 3.10 wt% H for 5 min, 4.14 wt% H for 10 min, 4.35 wt% H for 15 min, and 4.45 wt% H for 60 min at 593 K under 12 bar H2. From the beginning to about 10 min, the hydriding rate of the sample increased roughly as the number of cycles, n, increased. The quantity of hydrogen absorbed for 60 min, Ha (60 min), decreased on the whole as the number of cycles increased from 1 to 15. At n=15, MgH2-10Ni-2NaAlH4-2Ti absorbed 3.31 wt% H for 5 min, 3.60 wt% H for 10 min, 3.66 wt% H for 15 min, and 3.82 wt% H for 60 min. The quantity of hydrogen desorbed for 30 min, Hd (30 min), increased slowly as the number of cycles increased from n=2 to n=15. After hydriding-dehydriding cycling, β-MgH2, Mg, Mg2Ni, TiH1.924, NiAl, and MgO were observed in the samples. NiAl was formed from the reaction of Ni with Al which was formed by the decomposition of NaAlH4.